Pelatihan Literasi Digital (Cakap Dalam Menggunakan Media Teknologi Desa Penembang Kecamatan Merigi Kelindang Kabupaten Bengkulu Tengah - Alfatah , Dhika; Ridianto, Ridianto; Romdana, Romdana; Akmal, Samsul; Mulyadi, Mulyadi (Jurnal Semarak Mengabdi, 2024)
In this day and age, the use of technology has become very fast and massive, and today's technology users do not look at age and gender status with easy use. Digital is a form of modernization where everything can be done through sophisticated equipment to make people's affairs easier. This is what drives the way a person's perspective on living an increasingly sophisticated life today. The aim of writing the article is to present opportunities and challenges in building the character of the Penembang village community, who are competent with technology and digital literacy. Based on the research results, the research conclusion is that digital literacy has positive and negative impacts on each individual and society, depending on whether they can master the technology used today.